Photon correlation transients in a weakly blockaded Rydberg ensemble - Möhl, Charles; Spong, Nicholas L. R.; Jiao, Yuechun; So, Chloe; Ilieva, Teodora; Weidemüller, Matthias; Adams, Charles S. (Journal of physics. B, Atomic, molecular and optical physics, 2020)
The nonlinear and non-local effects in atomic Rydberg media under electromagnetically induced transparency (EIT) make it a versatile platform for fundamental studies and applications in quantum information. In this paper, we study the dynamics of a Rydberg-EIT system in an ensemble that allows for more than one Rydberg excitation in the propagation direction. The density of two-level atoms is such that transient superradiant effects occur. We experimentally observe a cross-over between coherent collective emission (‘flash’) of two-level atoms to a Rydberg dressed regime (‘dressed flash’) under EIT condition. The complex dynamics are characterised using both intensity and time correlation measurements. We show that while steady-state EIT gives a second order correlation g (2) = 0.79 ± 0.04, the Rydberg-dressed flash exhibits anti-bunching down to 0.2 ± 0.04.